Dynamics of Survival Strategy of Oil Palm Loading and Unloading Workers in Dasan Raja, Kota Subulussalam - Maya Sari; Nirzalin; Rizki Yunanda; Mursyidin; Muh. Fahrudin Alawi (Program Magister Administrasi Publik, 2025)
This study examines the Survival Strategy of Palm Oil Factory Workers (Case Study in Dasan Raja Village, Penanggalan District, Subulussalam City). The income of palm oil factory workers in Dasan Raja Village is not sufficient to meet family needs but they continue to work as palm oil workers in the village and through activities as a survival strategy. The focus of the problem in this study is the survival strategy of palm oil workers in Dasan Raja Village, Penanggalan District, Subulussalam City in meeting family needs and what causes palm oil workers to continue working in Dasan Raja Village, Penanggalan District, Subulussalam City. This study uses the Theory of Social Action according to Max Weber. The method used in this study is a qualitative research method with a descriptive approach. The results obtained from this study show the Survival Strategy of Palm Oil Workers, namely 1). Looking for Side Jobs, 2) Replacing Shifts 3). The Role of Other Family Members and 4). Utilizing Government Social Assistance. The reasons why palm oil stevedores continue to work are 1). Higher Wages and Lower Deductions 2). Limited Education and Skills 3). Social Relations and 4). Close to Home and Not Wanting to Migrate.